High-performance thermoplastic nanocomposites for aerospace applications: A review of synthesis, production, and analysis - Yilmaz, Sukran Guney; Ferik, Erdem; Birak, Selahattin Berat; Demirel, Merve Ozkutlu; Oz, Yahya; Kaboglu, Cihan (Sage Publications Ltd, 2026)
Thermoset polymers are cured under natural or synthetic created conditions and retain their solid form when exposed to heat. Unlike thermosets, thermoplastics melt when exposed to heat after production. Thermoplastics are preferred as raw materials because they can be easily shaped after production, have a high shelf life and are recyclable. In this regard, the prominence of high-performance engineering polymers in recent years has led to the preference of alternative polymers to thermosets. High-performance engineering thermoplastics include thermoplastics such as polyphenylene-sulfide (PPS), polyether-ether-ketone (PEEK), polyether-ketone-ketone (PEKK), polyphenylene-ether, polysulfone,polyoxadiazole, polyimide, polyether-amide, polyether-amide-imide, polynaphthalene, and polyamide-imide. These polymers exhibit application potential in aerospace, defense, automotive, marine, energy, and medical sectors. In challenging conditions such as high pressure, temperature, and corrosive environments, they possess high service temperatures, enhanced mechanical and physical properties, preferable chemical resistance as well as out-of-autoclave and rapid processing properties. In this review article, nanomaterial production methods (bottom-up and top-bottom) are mentioned. In the following sections, PPS, PEEK, and PEKK thermoplastics are explained, and carbon- and boron-based nano additives used in constructing nanocomposites are investigated. In the last section, PPS, PEKK, and PEEK polymer nanocomposites are investigated.
Keywords: Nano additives; nanocomposites; polyether-ether-ketone; polyether-ketone-ketone; polyphenylene-sulfide; thermoplastic polymers